Testing the robustness of the anthropogenic climate change detection statements using different empirical models. Issue 8 (29th April 2013) - Imbers, J.; Lopez, A.; Huntingford, C.; Allen, M. R.
Abstract : [1] This paper aims to test the robustness of the detection and attribution of anthropogenic climate change using four different empirical models that were previously developed to explain the observed global mean temperature changes over the last few decades. These studies postulated that the main drivers of these changes included not only the usual natural forcings, such as solar and volcanic, and anthropogenic forcings, such as greenhouse gases and sulfates, but also other known Earth system oscillations such as El Niño Southern Oscillation (ENSO) or the Atlantic Multidecadal Oscillation (AMO). In this paper, we consider these signals, or forced responses, and test whether or not the anthropogenic signal can be robustly detected under different assumptions for the internal variability of the climate system. We assume that the internal variability of the global mean surface temperature can be described by simple stochastic models that explore a wide range of plausible temporal autocorrelations, ranging from short memory processes exemplified by an AR(1) model to long memory processes, represented by a fractional differenced model. In all instances, we conclude that human‐induced changes to atmospheric gas composition is affecting global mean surface temperature changes. Key Points: Robustness tests of climate change detection and attribution Tests robustness under changes in depiction of internal variability Tests robustness under changes in forcing signals